Corticosterone increases intracellular Zn2+ release in hippocampal HT-22 cells. (19th February 2015) - Zheng, Yuanyuan; Huang, Junlong; Tao, Liping; Shen, Zhilei; Li, Hongxia; Mo, Fengfeng; Wang, Xiaoli; Wang, Shi; Shen, Hui
Highlights: CORT increased the intracellular Zn 2+ level. CORT increased the intracellular reactive oxygen species production. CORT decreased the intracellular ATP level. The increased intracellular Zn 2+ level by CORT is greatly dependent on intracellular Zn 2+ release. Abstract: The previous studies suggested that the hippocampal zinc dyshomeostasis and high glucocorticoid level might hurt hippocampal function. However, the effect of corticosterone (CORT) on hippocampus zinc homeostasis is not fully characterized. In this study, we investigated the intracellular Zn 2+ concentration in hippocampal HT-22 cells after CORT treatment. The cells were incubated with 10 μM CORT for 0 h–24 h, 0 μM–50 μM CORT for 6 h and 2.5 μM glucocorticoid receptor antagonist RU486 administered 30 min before CORT application. The results showed that 10 μM CORT increased the intracellular Zn 2+ level after 6 h, which was diminished by 2.5 μM RU486. Co-treatment of ZnSO4 and CORT augmented the increase in Zn 2+ level. TPEN, a membrane-permeable chelator for intracellular Zn 2+ greatly attenuated the Zn 2+ increase by CORT, while DTPA, a chelator for extracellular Zn 2+, had no same effects. CCK-8 tests demonstrated that 10 μM CORT treatment for 6 h had no inhibition effect on cells. However, intracellular reactive oxygen species (ROS) production increased and adenosine triphosphate (ATP) level decreased significantly after same CORT treatment, which was corrected by TPEN and aggravated by ZnSO4 . It could be suggested that the increased intracellular Zn 2+ by CORT was greatly dependent on intracellular Zn 2+ release, but not extracellular Zn 2+ intake. Meanwhile, our results demonstrated that increased intracellular Zn 2+ by CORT resulted in ROS generation and decreased ATP level in cells, which have possible roles in the hippocampal function disorder induced by stress.